The Effectiveness of Using Rational Judgment Strategy in Teaching Science on the Developing of Scientific Thinking at the Male Students of Intermediate Second Grade (Journal Of Educational and Psychological Researches, 2022)
The study aimed to explore the effectiveness of using rational judgment strategy in teaching science to develop scientific thinking for second-grade students. The researcher utilized the quasi-experimental approach based on (the pre/post designing) of two groups: experimental and control. As for tools: a test of scientific thinking prepared by the researcher that proved its verification of their validity and reliability. The test applied on a random sample of (66) students, divided into two groups: (34) experimental, and (32) control. The results showed that the experimental group outperformed the control group in the post-application of the scientific thinking test, In each skill separately, and in the total skills. The study recommended including a book in decision science teacher of middle school rational judgment and the steps of teaching it, training teachers to use the rational judgment strategy to develop the scientific thinking of their students.